Pathogenesis of involutional ectropion and entropion: the involvement of matrix metalloproteinases in elastic fiber degradation - Damasceno, Renato W.; Heindl, Ludwig M.; Hofmann-Rummelt, Carmen; Belfort, Rubens; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Holbach, Leonard M. (Orbit, 2011)
Purpose: To determine the elastic fiber content and ultrastructure as well as the expression of elastin-degrading enzymes in biopsy specimens from patients with involutional ectropion and entropion. Materials and Methods: Twenty consecutive patients with involutional ectropion (group 1) and twenty consecutive patients with entropion (group 2) were matched with twenty control patients (basal cell carcinoma) regarding age and gender. Full-thickness eyelid resections performed in study and control patients were examined by light and transmission electron microscopy, computer-assisted measurements, and immunohistochemistry using antibodies against matrix metalloproteinase (MMP)-2, MMP- 7, and MMP-9. The Kruskal-Wallis test and the Pearson chi-square test were performed. Results: Histopathologic analysis of the surgical specimens from patients with involutional ectropion and entropion showed a significant loss of elastic fibers in the eyelid skin, the pretarsal orbicularis oculi muscle, the perimeibomian tarsal stroma, and the intermeibomian tarsal stroma (P < 0.001). Residual elastic fibers revealed an abnormal ultrastructure. Immunohistochemistry demonstrated a significant overexpression of MMP- 2, MMP-7, and MMP-9 in the eyelid skin, the pretarsal orbicularis oculi muscle, the perimeibomian tarsal stroma, the intermeibomian tarsal stroma, and the conjunctiva in groups 1 and 2 compared to controls (P < 0.001). Conclusions: The present findings indicate that upregulation of elastolytic enzymes contributes to elastic fibre degradation in patients with involutional ectropion and entropion.
EVALuna2:21015